PENDAMPINGAN UMKM MAHASISWA SETU FARM DI ERA PANDEMI - Jaharuddin Jaharuddin; Adi Mansah; Hartutik Hartutik (Taksasila Edukasi Insani, 2025)
The economic crisis has had a significant impact on economic stability, as evidenced by the increasing number of layoffs due to business closures. In response to this challenge, innovation and creativity are essential to creating new business opportunities. Hafiz, a student from the Management Study Program, Faculty of Economics and Business, Universitas Muhammadiyah Jakarta, addressed this issue by establishing a catfish farming business named